2016
DOI: 10.1364/boe.8.000407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic imaging and quantitative analysis of cranial neural tube closure in the mouse embryo using optical coherence tomography

Abstract: Abstract:Neural tube closure is a critical feature of central nervous system morphogenesis during embryonic development. Failure of this process leads to neural tube defects, one of the most common forms of human congenital defects. Although molecular and genetic studies in model organisms have provided insights into the genes and proteins that are required for normal neural tube development, complications associated with live imaging of neural tube closure in mammals limit efficient morphological analyses. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…For example, OCT is capable of imaging blood vessels less than 50 μm in diameter, which other modalities such as ultrasound biomicroscopy are incapable of resolving . We have demonstrated the superior capabilities of OCT for mouse and rat embryonic imaging during normal and abnormal development .…”
Section: Introductionmentioning
confidence: 96%
“…For example, OCT is capable of imaging blood vessels less than 50 μm in diameter, which other modalities such as ultrasound biomicroscopy are incapable of resolving . We have demonstrated the superior capabilities of OCT for mouse and rat embryonic imaging during normal and abnormal development .…”
Section: Introductionmentioning
confidence: 96%
“…By imaging different regions of the neural tube at different developmental stages of the murine embryo, we hope to study how changes in mechanical properties of cells influence NTDs. Since OCT has already been used for imaging and analyzing the closure of a live murine embryonic neural tube, 58 our future work will entail imaging this process with Br-OCT and understanding the influence of teratogens and other environmental factors on neural tube closure.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies concerned sections of mouse embryos (Sadler, ; Greene and Copp, ; Pyrgaki et al, ), but the presented figures remain inconclusive to show multiple sites of fusion within one embryo since the successive sections are lacking or the neural walls lie closely together but show no fusion. Also, the stunning dynamic images of neural tube closure in mouse embryos of Pyrgaki and Wang did not display this kind of fusion (Pyrgaki et al, ; Wang et al, ). The electron microscope images published by Juriloff et al (), however, showed a degree of fusion that is significant enough to consider that neural tube closure in mouse embryos occurs at multiple sites.…”
Section: Materials and Methods And Resultsmentioning
confidence: 99%